gamma-ray emission from the Perseus cluster of galaxies observed with the MAGIC telescopes - Colin, P.; Eisenacher, D.; Hildebrand, D.; Lombardi, S.; Lindorfs, E.; Paneque, D.; Partini, S.; Prada, F.; Sitarek, Julian; Zandanel, F.; Dauser, Thomas; Kadler, M.; et al. (2012)
The Perseus cluster of galaxies is a nearby cool-core cluster with an intra-cluster medium (ICM) characterized by very high central densities. The observation of the Perseus cluster with the MAGIC telescopes, during 85 h from 2009 to 2011, resulted in the discovery of 2 point-like sources at very high energy (>100GeV, VHE) coinciding with the central radio galaxy NGC1275 and the radio galaxy IC 310. The gamma-ray properties of these 2 sources are presented, taking into account contemporaneous Fermi-LAT as well as multi-wavelength data. Flux variability and spectral energy distribution shapes indicate that the VHE gamma-rays do not originate from large-scale interaction of the radio galaxies with ICM but more likely from the active nuclei of these two galaxies. They could be both misaligned version of BL Lac objects, the most common TeV AGN. Our results provide vital clues to understand emission mechanisms of such misaligned objects, and how they may be related to the beamed emission seen in BL Lacs. No evidence of large-scale VHE gamma-ray emission from hadronic cosmic ray (CR) interactions with the ICM has been found. The flux upper limit above 1 TeV reaches the signal expected by some theoretical models, constraining the cluster CR physics. In the framework of the hadronic model of the radiomini-halos, this limit implies a minimal magnetic field ranging from 4-9 mu G for the central cluster region.
Keywords: gamma-ray astronomy; Galaxy Cluster; Radio galaxy; NGC 1275; IC 310; Cosmic rays